2022
DOI: 10.1007/s10533-022-00990-0
|View full text |Cite|
|
Sign up to set email alerts
|

Size matters: biochemical mineralization and microbial incorporation of dicarboxylic acids in soil

Abstract: The transformation and turnover time of medium- to long-chain dicarboxylic acids (DCA) in soil is regulated by microbial uptake and mineralization. However, the chain length of n-alkyl lipids may have a remarkable influence on its microbial utilization and mineralization and therefore on the formation of stable soil organic carbon from e.g. leave- needle- and root-derived organic matter during decomposition. To investigate their size dependent mineralization and microbial incorporation, four DCA of different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…2 , Table S1 ) suggested that these biomarkers are preserved in soil without significant alteration of 13 C signatures. The δ 13 C values of C 28 further indicate that long-chain diFAs are very stable in the soil due to the high energy requirement for uptake by microorganisms (Kashi et al 2023 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 , Table S1 ) suggested that these biomarkers are preserved in soil without significant alteration of 13 C signatures. The δ 13 C values of C 28 further indicate that long-chain diFAs are very stable in the soil due to the high energy requirement for uptake by microorganisms (Kashi et al 2023 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Although long-chain (C 20 –C 32 ) α,ω-dicarboxylic fatty acids (diFAs) comprise about 0.3% of total soil lipids (Holtvoeth et al 2016 ), they are a major component of suberin (Serra and Geldner 2022 ). Given their chain length-dependent hydrophobicity, the degradation of diFAs in soil decreases with increasing chain length (Kashi et al 2023 ). Therefore, these diFAs are considered very robust indicators of root inputs to soils (Mendez-Millan et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%